2016
DOI: 10.1016/j.jpain.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Is Pain Perception Altered in People With Depression? A Systematic Review and Meta-Analysis of Experimental Pain Research

Abstract: This meta-analysis of experimental studies suggests potential effects of depression on pain perception are variable and likely to depend upon multiple factors. The contrasting pattern for ischemic versus other noxious stimuli suggests that stimulus modality is a key factor, which could help explain discrepancies across clinical and experimental findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 69 publications
3
90
1
5
Order By: Relevance
“…In contrast, a recent meta-analysis found that depressed patients had higher experimental pain thresholds than controls, while pain tolerance was not different. 51 However, it is important to note that patients in our study generally showed low to moderate depressive symptoms and would not meet the criteria for a depressive disorder. Our study extends these findings and has addressed the contribution of depression to ethnic group differences in clinical pain and experimental pain sensitivity between Asian Americans and NHWs.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, a recent meta-analysis found that depressed patients had higher experimental pain thresholds than controls, while pain tolerance was not different. 51 However, it is important to note that patients in our study generally showed low to moderate depressive symptoms and would not meet the criteria for a depressive disorder. Our study extends these findings and has addressed the contribution of depression to ethnic group differences in clinical pain and experimental pain sensitivity between Asian Americans and NHWs.…”
Section: Discussionmentioning
confidence: 66%
“…In a recent meta-analysis of experimental studies, Thompson et al97 concluded that potential effects of depression on pain perception are variable and likely to depend upon multiple factors, including the stimulus modality. This conclusion could help explain the discrepancies across clinical and experimental findings;97 however, further studies on the links between depression and pain perception area are needed in all age groups, including the elderly.…”
Section: Perception Of Pain and The Role Of Depressionmentioning
confidence: 99%
“…Extraction and coding of study data was performed by two authors (TT, KG), on a standardized form adapted from our previous studies [53,57] A number of decisions were made when computing effect sizes from extracted data. First, a few studies (k=3) provided data from multiple independent participant samples [3,48,61], e.g.…”
Section: Data Extractionmentioning
confidence: 99%
“…A random-effects model was chosen as heterogeneity was expected based on similar meta-analyses conducted for other disease conditions [53,57]. Several studies reported multiple ES data from the same samples and a few studies used different PD sample but with the same control group comparisons.…”
Section: Meta-analysismentioning
confidence: 99%